(untitled) (MAUSAM, 1971)
Recent information, though not very adequate, about cumulonimbus cloud heights are available in India, from post flight reports of civil jet airliners and meteorological reconnaissance flights organised by Air Force. In the present paper, results of radar study of the heights of Ob cloud tops in the Brahmaputra valley, based on hourly radarscope observations, for pre-monsoon and monsoon months of 1967. 1968, 1969 and 1970 have been reported.